Photocatalytic decolorization of basic Red 46 using immobilized TiO2 nanoparticles onto rice husk ash - Nur Hidahyu Azman (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The presence of BR 46 in wastewater represents significant environmental problem. Photocatalysis acts as an alternative due to some drawbacks in conventional wastewater treatment. Immobilized TiO2 nanoparticles photocatalyst was successful synthesized using modified sol-gel method. The decolorization of Basic Red 46 was investigated in a batch reactor. The synthesized photocatalyst was characterized using Scanning Electron Microscope (SEM). The effect of initial dye concentration, pH and photocatalyst dosage has been investigated and the optimized conditions for maximum amount of decolorization were determined using Response Surface Methodology (RSM). The optimum Basic red 46 decolorization was achieved with the optimal condition of 2.5 g/L, initial dye concentration of 20 mg/L at pH 11.